PENEGAKAN HUKUM TERHADAP ORANG YANG MENYEDIAKAN TEMPAT PERJUDIAN BAGI PELAKU TINDAK PIDANA PERJUDIAN DI WILAYAH HUKUM RESOR SAMOSIR PROVINSI SUMATRA UTARA - Sitio, Goltiar; Firdaus, Emilda; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Gambling is essentially an act that is challenged by the norms of religion, morality, morality and legal norms and endangers the lives of people, nations and countries. In society the act of playing gambling has been considered a habit that does not violate the law. It is quite alarming when people tend to take the gambling action. the cause of the community taking action in gambling is the availability of gambling places in the community, which has resulted in many people committing criminal acts of gambling, but the police as law enforcers only taking action against gambling players is not accompanied by law enforcement against people who provide gambling. Therefore law enforcement for people who provide gambling places for gambling offenders has not been implemented, which has resulted in an increase in the number of gambling cases in the community. This research is sociological legal research that is research that wants to see the unity between law and society with the gap between das sollen and das sein. This research was conducted in the jurisdiction of the Samosir Resort Police, while the population and samples were all parties related to the problems examined in this study, as much data was used, primary data, secondary data and tertiary data, data collection techniques in this study were carried out through interview and literature review. From the results of the research conducted. First is preventive (repressive) and repressive (enforcement) law enforcement. The second obstacle faced by law enforcers against people who provide gambling sites is that the perpetrators of gambling hide information that involves providers of gambling, the public does not want to report, intervention from certain elements, lack of police infrastructure, information on raids that leak to the community, incomplete law enforcement in the Samosir region. Third is law enforcement efforts to eradicate gambling and gambling providers. By internally improving the quality of the Samosir Resort Police and taking efficient and effective actions in handling criminal acts, externally taking action against providers of gambling sites, often patrolling and forming Intel to monitor whether gambling has occurred in the community. Keywords: Law Enforcement - Crime - Gambling and Providing Gambling Sites